Female Directors and Firm Performance: Evidence from UK Listed Firms - Pananda Pasaribu (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2017)
The impact of female directors on firm performance has lacked consistency in the previously conducted empirical studies, which may be due to the endogeneity problem, or certain characteristics (i.e. governance, industry, competition). This study examines the relationship between female directors and firm performance by addressing those problems. This study analyses all non-financial UK listed firms during the period 2004-2012 and employs several econometric models. The regression results indicate that there is little evidence that female directors have a positive and strong relationship with firm performance. But, further analysis reports that the UK’s small listed firms experience a positive significant effect, because small firms do not suffer from the problem of over-monitoring and they have more flexibility in composing their boards of directors.